Pengaruh Prenatal Yoga terhadap Penurunan Nyeri Punggung pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Kedondong Kabupaten Pesawaran - Deya Panesa; Juwita Desri Ayu; Eka Tri Wulandari; Riona Sanjaya (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Back pain is a common complaint experienced by third-trimester pregnant women due to physiological changes such as weight gain, postural changes, and ligament relaxation. This condition can interfere with comfort and daily activities, therefore requiring safe and effective management, one of which is a non-pharmacological therapy in the form of prenatal yoga. This study aimed to determine the effect of prenatal yoga on reducing back pain among third-trimester pregnant women in the working area of Kedondong Public Health Center, Pesawaran Regency, in 2025.This study employed a quantitative method with a One Group Pre-Test Post-Test design. The sample consisted of 26 third-trimester pregnant women selected through random sampling. Back pain intensity was measured using the Numeric Rating Scale (NRS) before and after the prenatal yoga intervention. Data analysis was conducted using the Wilcoxon test because the normality test results indicated that the data were not normally distributed (p < 0.05). The results showed that the mean back pain score before the intervention was 6.04 (moderate–severe category) and decreased to 3.04 (mild–moderate category) after the intervention. All respondents (100%) experienced a reduction in back pain, with 26 negative ranks and no positive ranks or ties. The Wilcoxon test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant effect of prenatal yoga on reducing back pain in third-trimester pregnant women. In conclusion, prenatal yoga is effective in reducing back pain among third-trimester pregnant women and can be recommended as a safe and beneficial non-pharmacological intervention in antenatal care services to improve maternal comfort.